2019
DOI: 10.5194/asr-16-31-2019
|View full text |Cite
|
Sign up to set email alerts
|

Communicating the amount of windstorm induced forest damage by the maximum wind gust speed in Finland

Abstract: Abstract. Windstorms are natural disturbance agents in forests playing a role in natural forest regeneration. In Finland, the most severe individual windstorms have commonly damaged 2–4 million m3 of timber. In addition to financial losses caused to forest owners, windthrown trees have in many cases seriously disrupted the functionality of the national power grid. Communicating windstorm risks in duty forecasting is difficult. In this study, we aimed at developing windstorm impact estimates for forest damage i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 19 publications
5
29
0
1
Order By: Relevance
“…Based on our study, significant differences were seen along the west, northwest, and north directions for the critical wind speeds and consequently wind speeds needed for the damage at certain forested point at the local meteorological station (Table 3). This is inline with the fact that recent storms over the study area had tracks along those directions (Valta et al 2019). Also, the distance to upwind stand edge was a significant variable (p value is 0.0642).…”
Section: The Utility Of Als and Aerial Image Data In Wind Damage Risksupporting
confidence: 72%
See 2 more Smart Citations
“…Based on our study, significant differences were seen along the west, northwest, and north directions for the critical wind speeds and consequently wind speeds needed for the damage at certain forested point at the local meteorological station (Table 3). This is inline with the fact that recent storms over the study area had tracks along those directions (Valta et al 2019). Also, the distance to upwind stand edge was a significant variable (p value is 0.0642).…”
Section: The Utility Of Als and Aerial Image Data In Wind Damage Risksupporting
confidence: 72%
“…Hence, accurate projections of future windstorm climate are essential. In general, for the present climate, most wind storms over the study area are either along the west, northwest, or north directions, although rare easterly wind storms also occur (Valta et al 2019). In a recent study by Ruosteenoja et al (2019), it was found out that climate change will not have any major impact on wind direction during wind storm events.…”
Section: Relevance Of Wind Climate and Directionmentioning
confidence: 74%
See 1 more Smart Citation
“…Tämä johtuu pitkälti siitä, että myrskyn tuhovoima kasvaa nopeasti tuulen nopeuden voimistuessa. Suomessa on arvioitu, että sulan maan aikana tyypillinen laaja-alainen myrsky, jossa tuulen suunta on lännen tai luoteen puolelta, aiheuttaa karkeasti noin 0,3 miljoonan kuution metsätuhot, jos maa-alueiden voimakkaimmat tuulen puuskat ovat 25 m/s, mutta jos voimakkaimmat puuskat puhaltavatkin 30 m/s, puustotuhoja tulee jo noin 1,9 miljoonaa kuutiota ja 35 m/s tuulen puuskilla tuhot kasvavat noin 8,7 miljoonaan kuutioon (Valta et al, 2019). Esimerkiksi hieman Tapania voimakkaampi, mutta selvästi mittavammat metsätuhot aiheuttava myrsky on meillä ilmastonmuutoksesta riippumatta täysin mahdollinen.…”
Section: Myrskyt Ja Rajuilmatunclassified
“…Thus one storm object represents a solid area (polygon) where hourly maximum wind gust exceeds 15 m s −1 during one particular hour. The threshold of 15 m s −1 is selected as different sources indicate Finland being vulnerable for windstorms and rather moderate winds (from 15 m s −1 ) causing damages to forests (Valta et al, 2019;Gardiner et al, 2013). To estimate the windstorm impacts on forests, Valta et al (2019) developed a method by combining the recorded forest damages from the nine most intense storms and their observed maximum inland wind gusts.…”
Section: Identifying and Tracking Storm Objectsmentioning
confidence: 99%